The Relationship of Risk Factors to the Incidence of Hypertension in Pre-Elderly and Elderly (Study in Ternate City) - The, Fera; Hasan, Marhaeni; Imbar, Andri; Dika, Sadrakh (Journal of The Community Development in Asia, 2023)
hypertension, is a chronic disease. Every day, the number of cases of hypertension in pre-elderly and elderly is increasing, and it can have a variety of consequences, including: reduced quality of life, difficulties in social and physical functioning, and increased pain and mortality due to complications. This study aims to identify the relationship between risk factors and the incidence of hypertension in the elderly and geriatric population in the city of Ternate. This study was a cross-sectional study using univariate and bivariate analyzes, to determine the relationship between risk factors and the incidence of hypertension in pre and elderly individuals. Samples were selected by cluster random sampling technique and using blood pressure checks and questionnaires containing structured questions. This study was conducted in the Ternate Public Health Center (PUSKESMAS) with 299 respondents from pre-elderly and elderly aged ≥45 years old. The research uncovered five factors that with a significant relationship with hypertension. Those factors are age, family history, salt intake, obesity, and dyslipidemia. On the other hand, there are three factors that have no significant relationship with hypertension, which is gender, smoking habits, and alcohol consumption.